PENYULUHAN PEMANFAATAN TANAMAN HERBAL DI LINGKUNGAN SEKITAR SEBAGAI OBAT TRADISIONAL DI SMA NEGERI 1 PANCUR BATU - Sembiring, Pintata (INSTITUT KESEHATAN DELI HUSADA, 2023)
Herbal plants are plants that have been identified and known based on human observation to have compounds that are useful for preventing and curing disease. Traditional medicine is an ingredient or concoction of ingredients in the form of plant ingredients, animal ingredients, mineral ingredients, extract preparations (galenic), or mixtures of these ingredients which have been used for treatment for generations. Secondary metabolite compounds commonly found in plants are flavonoids, alkaloids, saponins, phenols, tannins, steroids and triterpenoids. Flavonoids are a group of polyphenols and are classified based on their chemical structure and biosynthesis. One of the plants that can be used as traditional medicine is the Sirih cina (Peperomia pellucida L. Kunth) . The aim of this counseling is to increase knowledge about the use of herbal plants and increase students' knowledge about traditional medicine in the surrounding environment as traditional medicine at SMA Negeri 1 Pancur Batu. After participating in this outreach activity, it is hoped that students will be able to increase their knowledge and level of health where students will be able to take part in educating friends and family regarding the importance of using medicinal plants as traditional medicine as an effort to maintain health by utilizing plants around them.